Magnetic properties of NiCuZn ferrites synthesized by oxalate precursor method - Ghodake, S. A.; Ghodake, U. R.; Sawant, S. R.; Suryavanshi, S. S.; Bakare, P. P. (Journal of Magnetism and Magnetic Materials, 2006)
Ni-Cu-Zn ferrites have been synthesized by employing co-precipitation technique using oxalate precursors. X-ray diffractograms did not show impurity phases, indicating single-phase formation of the ferrites. The diffractograms of oxalate complex decomposed at 650 degrees C show that ferritization is complete up to 650 degrees C. Lattice parameter a (angstrom) was found to decrease with the addition of Ni2+ which is attributed to ionic sizes of Ni2+ (0.69 angstrom), which replaces Cu2+ (0.72 angstrom). From the thermogravimetric studies it is observed that the experimentally observed total mass loss (%), agrees with theoretically calculated mass loss (%) indicating maintenance of requisite stoichiometry. Initial permeability (mu(i)) shows increase when Ni2+ is added up to x = 0.15 while for (x > 0. 15), it decreases. The increase in initial permeability (mu(i)) is attributed to monotonic increase in Ms, and K-1 on addition of Ni2+. However, the microstructure and density (porosity) also influence mu(i) variations. The decrease in pi is attributable to increase of K-1. The composition with density 91.14% exhibits large mu(i) which also tends to increase with temperature up to 60 degrees C. Thus its usable range extends up to 60 degrees C. This samples has T-c near to 160 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: initial permeability; magneticproperties; Magnetization; NiCuZn ferrites; XRD

Complex permeability studies of Ni-Co-Zn ferrites synthesized by an oxalate precursor method - Ghodake, J. S.; Kambale, R. C.; Kulkarni, S. D.; Sawant, S. R.; Suryavanshi, S. S. (Smart Materials & Structures, 2009)
Nanocrystalline Co-substituted Ni-Zn ferrites have been synthesized by employing a co-precipitation technique using oxalate precursors. The co-precipitated oxalates were decomposed in air at 650 degrees C for 1 h and the powder was sintered at 1000 degrees C. The phase formation of the sintered ferrite was confirmed by x-ray diffraction studies. The lattice parameter a (angstrom) increases with the addition of Co(2+) which is attributed to the large ionic size of Co(2+) (0.78 angstrom), which replaces Ni(2+) (0.74 angstrom). The crystallite size has been estimated by the Debye-Scherrer formula using the full width at half-maximum (FWHM) of the line broadening of the (311) reflection and it is found to be in the range of 25-28 nm. Also, with increasing cobalt content the magnetocrystalline anisotropy constant (K(1)) and magnetostriction constant (lambda(s)) increase, and the grain size decreases, hence the value of initial permeability mu(i) decreases. The saturation magnetization M(s) and magnetic moment (n(B)) do not show any significant variation for all compositions varying with the cobalt content.

Nanostructured nickel ferrite: a liquid petroleum gas sensor - Darshane, Sonali L.; Suryavanshi, S. S.; Mulla, Imtiaz S. (Ceramics International, 2009)
The present investigation deals with the synthesis of nanostructured nickel ferrite (NiFe(2)O(4)) and their liquid petroleum gas-sensing characteristics. The 15-20 nm size nickel ferrite has been synthesized at 700 degrees C by a simple molten-salt route using sodium chloride as grain growth inhibitor. These nanoparticles exhibit significantly high response towards liquid petroleum gas (LPG) in comparison with ethanol vapor, hydrogen sulfide, ammonia and hydrogen. The gas response towards various gases at their 200 ppm concentrations is investigated at 200-450 degrees C. Different characterization techniques have been employed, such as differential thermal analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM) to study the crystallite size, structure and morphology. The results suggest possibility of utilization of the nanostructured nickel ferrite, without addition of any precious metal ion, as the LPG detector. (c) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrites; nanomaterial; Sensor; Spinels

Influence of Pd-loading on gas sensing characteristics of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Nanocrystalline pristine and 0.5, 1.5 and 3.0 wt% Pd loaded SnO2 were synthesized by a facile co-precipitation route. These powders were screen-printed on alumina substrates to form thick films to investigate their gas sensing properties. The crystal structure and morphology of different samples were characterized by using X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The 3.0 wt% Pd:SnO2 showed response of 85% toward 100 ppm of LPG at operating temperature of 250 degrees C with fast response (8 s) and quick recovery time (24 s). The high response toward LPG on Pd loading can be attributed to lowering of crystallite size (9 nm) as well as the role of Pd particles in exhibiting spill-over mechanism on the SnO2 surface. Also selectivity of 3.0 wt% Pd:SnO2 toward LPG was confirmed by measuring its response to other reducing gases like acetone (CH3COCH3), ethanol (C2H5OH) and ammonia (NH3) at optimum operating temperature. (C) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: LPG sensor; Palladium; SnO2; Thick film

Studies on the resistive response of nickel and cerium doped SnO2 thick films to acetone vapor - Bagal, L. K.; Patil, J. Y.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2012)
Undoped and Ni, Ce-doped nanocrystalline tin oxide were synthesized by co-precipitation route. Doped as well as undoped SnO2 compositions revealed single phase structure without any impurity. The lattice constant of SnO2 increases and the grain size decreases with doping of Ni and Ce. The responses of the sensing elements are evaluated by measuring the resistance change upon exposure to various test gases such as liquid petroleum gas (LPG), acetone, ethanol and ammonia. In comparison to LPG, ethanol, and ammonia the response towards acetone vapor increases markedly on simultaneous doping of Ni and Ce. For acetone vapors with 500 ppm at 300 degrees C, the undoped SnO2 shows 31% response, while with individual Ni or Ce doping it increases to 38 and 60%, respectively, however with simultaneous doping of Ni and Ce there is a significant enhancement up to 92%. The results of gas sensing measurements reveal that the thick films deposited on alumina substrates using screen printing technique give selectively a high response of (87%) with fast recovery (similar to 1 min) towards 100 ppm acetone at 300 degrees C. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: (Ni plus Ce)-doping; Acetone vapor; Screen-printing; SnO2

Acetone vapour sensing characteristics of undoped and Zn, Ce doped SnO2 thick film gas sensor - Bagal, L. K.; Patil, J. Y.; Bagal, K. N.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Materials Research Innovations, 2013)
The nanocrystalline materials of zinc and ceria doped tin oxide [(Zn+Ce)-SnO2] powders were synthesised by coprecipitation method and investigated for their sensing properties towards liquid petroleum gas (LPG), ethanol, ammonia and acetone vapour. The crystal structure and phase of the as synthesised and sintered powders were characterised by X-ray diffractometer and the microstructure by scanning electron microscopy. All the doped and undoped SnO2 compositions revealed single phase solid solution formation. Transmission electron microscope results indicated that well crystallised (Zn+Ce) doped SnO2 particles of size similar to 7 nm were obtained at the annealing temperature of 650 degrees C. The reduction in grain size of the metal oxide is a key factor to enhance the gas sensing properties. The doping of zinc, ceria in SnO2 has reduced the grain size and improved the gas response. The results of gas sensing measurements showed that the thick films deposited on alumina substrates using screen printing technique exhibited high response to acetone at an operating temperature of 300 degrees C. Further, the selectivity of the sensor towards acetone with respect to other reducing gases (LPG, ethanol and ammonia) was studied.
Keywords: Gas; Screen printing; Sensor; SnO2

Liquefied petroleum gas sensing performance of cerium doped copper ferrite - Khandekar, M. S.; Tarwal, N. L.; Patil, J. Y.; Shaikh, F. I.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2013)
Undoped and cerium (Ce) doped nanocrystalline copper ferrite (CuFe2O4) materials were synthesized via the molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CuFe2O4 ferrite have been investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CuFe2O4. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Moreover, the gas sensing properties of sintered samples were studied towards different reducing gases such as liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sample with 4% cerium doped CuFe2O4 (Ce4) showed the maximum gas sensitivity (86%) towards LPG with fast response time of 5 s and good recovery time of 68 s. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrite; Gas sensor; Molten-salt method; TEM

Nanocrystalline Ce doped CoFe2O4 as an acetone gas sensor - Khandekar, M. S.; Tarwal, N. L.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Ceramics International, 2014)
Nanocrystalline CoFe2-xCexO4 ferrites (x=0, 0.04, 0.08) were synthesized by using the inexpensive, simple and eco-friendly molten-salt (M-S) method. Effects of Ce doping on the structural, morphological and gas sensing properties of the CoFe2O4 ferrite were investigated. X-ray diffraction (XRD) analysis revealed the formation of spinel CoFe2O4. Transmission electron microscopy (TEM) investigations showed that the synthesized ferrite is made up of very fine spherical nanoparticles. Furthermore, the gas response of nanocrystalline ferrite materials was investigated in the temperature range of 200-450 degrees C toward the reducing gases like liquefied petroleum gas (LPG), acetone, ethanol and ammonia. The sensor response was found to be sensitive and selective toward acetone as compared to other reducing gases. It is observed that the addition of Ce (4 wt%) strongly influenced the response and the operating temperature of the sensor material and thus can serve as acetone-sensing sensors. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: CoFe2O4; Ferrite; Gas sensor; Molten-salt method; TEM

Effect of Pd and Ce on the enhancement of ethanol vapor response of SnO2 thick films - Bagal, L. K.; Patil, J. Y.; Vaishampayan, M. V.; Mulla, Imtiaz S.; Suryavanshi, S. S. (Sensors and Actuators B-Chemical, 2015)
The undoped SnO2 and 4 wt% Ce-doped SnO2 were successfully synthesized by a facile co-precipitation route. The ternary systems were prepared by Pd-loading (0.5, 1.5 and 3.0 wt%) on the 4 wt% Ce-doped SnO2 nanoparticles. The structure and morphology of the nanocrystalline powders were investigated by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques. The nanocrystalline powders were screen printed on the alumina substrates to form thick films to investigate their gas response properties. The gas response studies reveal that 4 wt% Ce-doped SnO2 with the loading of 3.0 wt% Pd exhibits high response (88%) towards ethanol (100 ppm) at an operating temperature of 250 degrees C with quick response (6 s) and rapid recovery (20 s). The high ethanol vapor response at lower operating temperature of this sensor is attributed to the spill-over mechanism of Pd particles present on the SnO2 surface and enhancement in alkalescence of SnO2 due to Ce-doping. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Ce-doped tin oxide; Gas sensor; Semiconductor; Thick film

Enhanced energy density and stability of self-assembled cauliflower of Pd doped monoclinic WO3 nanostructure supercapacitor - Gupta, S. P.; Patil, V. B.; Tarwal, N. L.; Bhame, S. D.; Gosavi, S. W.; Mulla, I. S.; Late, D. J.; Suryavanshi, S. S.; Walke, P. S. (Materials Chemistry and Physics, 2019)
Enhanced electrochemical performance of WO3 nanostructures by engineering their morphology, structural and surface defect at nanoscale is feasible. Herein we report the effect of Pd doping on the morphological and electrochemical properties of WO3 at nanoscale prepared by a simple hydrothermal method. The synthesized pristine WO3 (cabbage like morphology) and Pd doped WO3 (cauliflower like morphology) are examined by using XRD, XPS, Raman spectra, BET, FE-SEM, TEM. The morphological investigation shows the effective rebuilding of nanosheets assembled cabbage shaped pristine WO3 into nanobricks assembled cauliflower shaped Pd doped WO3 with improvement in crystallinity, surface area and conductivity. As a result, the enhancement in the electrochemical performance of cauliflower shaped Pd-WO3 is recorded four times higher specific capacitance than pristine WO3. Additionally, the excellent cyclic stability (almost ten times higher than pristine WO3) up to 1100 cycles with nearly 86.95% capacity retention is observed in Pd-WO3 attributed to Pd content and highly modified structural arrangement.